When sounds come alive: animacy in the auditory sense - Gonan, Stefano; Vallortigara, Giorgio; Chiandetti, Cinzia (Frontiers in Psychology, 2024)
Despite the interest in animacy perception, few studies have considered sensory modalities other than vision. However, even everyday experience suggests that the auditory sense can also contribute to the recognition of animate beings, for example through the identification of voice-like sounds or through the perception of sounds that are the by-products of locomotion. Here we review the studies that have investigated the responses of humans and other animals to different acoustic features that may indicate the presence of a living entity, with particular attention to the neurophysiological mechanisms underlying such perception. Specifically, we have identified three different auditory animacy cues in the existing literature, namely voicelikeness, consonance, and acoustic motion. While the first two characteristics are clearly exclusive to the auditory sense and indicate the presence of an animate being capable of producing vocalisations or harmonic sounds -with the adaptive value of consonance also being exploited in musical compositions in which the musician wants to convey certain meanings -acoustic movement is, on the other hand, closely linked to the perception of animacy in the visual sense, in particular to self-propelled and biological motion stimuli. The results presented here support the existence of a multifaceted auditory sense of animacy that is shared by different distantly related species and probably represents an innate predisposition, and also suggest that the mechanisms underlying the perception of living things may all be part of an integrated network involving different sensory modalities.